Hubungan Pengetahuan dengan Sikap Tentang Sadari pada Remaja Putri Kelas X di MAN 3 Sleman - Zilvitanafiandina Zilvitanafiandina; Belian Anugrah Estri (Pusat riset dan Inovasi Nasional, 2026)
According to the International Agency for Cancer Registry (IACR), breast cancer is the most common cancer among women after lung cancer, and continues to be frequently diagnosed worldwide. In 2022, more than 2.32 million new cases of breast cancer were reported globally, while Indonesia recorded 65,858 cases (16.6% of all cancers). Therefore, adolescent girls need to have adequate knowledge and a positive attitude toward breast self-examination (BSE/SADARI) as part of reproductive health awareness and preventive efforts. This study aims to examine the relationship between knowledge and attitudes regarding SADARI among 10th-grade female students at MAN (State Islamic Senior High School) 3 Sleman. This study employed a quantitative correlational approach with a cross-sectional design, involving a sample of 66 respondents. Data were collected using a questionnaire containing questions related to BSE. The Spearman Rank test showed a p-value of 0.606, which is greater than 0.05 (p > 0.05). This indicates that there is no significant relationship between the level of knowledge and attitudes toward BSE among 10th-grade female students at MAN 3 Sleman. In addition, the correlation coefficient (r) was 0.065, indicating a very weak relationship between knowledge and attitudes. There is no significant relationship between knowledge and attitudes regarding BSE among 10th-grade female students at MAN 3 Sleman. Schools and healthcare providers are encouraged to enhance structured and continuous BSE education and incorporate educational media during health counseling to foster positive attitudes.